PROTOTIPE SISTEM INFORMASI BIAYA PENYUSUTAN ASET TETAP MENGGUNAKAN METODE GARIS LURUS DAN PENENTUAN AKHIR MASA MANFAAT DALAM MANAJEMEN ASET - Eko Purwanto; Indra Hastuti; Sri Ningrum (Politeknik Indonusa Surakarta, 2019)
Data processing fixed assets include recording and calculating depreciation of fixed assets is not computerized. In preparing the report, it is also not fast enough and accurate. The purpose of this study to simplify and streamline the process data fixed assets so that the work can be completed on time with a precise and accurate results. The applications to be built is a desktop-based and multi user which each user has the authority according to his or her rights. Methods of data collection using observation, book study method, and the method of interview. This information system development using the waterfall while the data flow method is structured method DFD (Data Flow Diagram) in illustrating functional model and ERD (Entity Relationship Diagram) to illustrate data model . The programming language is using Visual Basic.Net with MySQL Database applications . The information system cost of depreciation of fixed assets can calculate the depreciation by the straight-line method and determine the end of fixed assets benefit and result reports of fixed assets depreciation, complete with the economic life, depreciation rates, accumulated depreciation, book value and expiration of the useful life of fixed assets.